The Effect Of Using Different Types Of Chili On The Quality Of Beef Rendang - Melani, Cut; Syarif, Wirnelis (Jurnal Pendidikan Tata Boga dan Teknologi, 2022)
This research is motivated by the exsistence ov various types of chili that use by the community in processing beef rendang, so that will be produces a different taste of rendang. The use of different types of chili because the local people use the chili according to what is grown and available chili in their respectives areas. Each type of chili has a different capsaicin content. Capsaicin is a compound that causes a spicy taste and provides warmth. The level of capsaiciness on the chili is measured by the scoille. The higher of capsaicin content in the chili makes hotter that chili taste. In this study, the types of chili that used to made beef rendang are divided in two, namely round red chilies and churly red chilies. Round red chili has a less spicy taste while curly red chily. This types of resecarh is an experiment with organoleptic test. The experimental was carried oy 3 expert panelists. Furthermore, the data was processed by the pooled variance T test (t test). The result showed that there was an average effect of using different types of chilion the quality of the bran spicy tase was 2,89 and 3,87. No significant effect on the quality of forms 3,33; inside of meet 3,89 and 3,78; bran color in 3,11 and 3,33; same aromas in 4; same meat texture 3,56; bran texture in 3,22 and 3,11; meat taste in 3,67 and 3,68 and the bran savory taste is 3,89 and 3,78